Improving Employee Performance through IT Engagement: The Roles of Individual Experience and Management Support - Lavianti, Desi; Munir, Munir; Dirgantari, Puspo Dewi; Rasim, Rasim; Mahphoth, Mohd Halim bin (Jurnal Manajemen Bisnis, 2025)
Research aims: Employee IT engagement is a critical component in the successful implementation of digital transformation. Both prior IT experience and support from upper management significantly influence the extent of employee involvement in IT. This study aims to explore the relationship between employee IT engagement, management's support, and understanding of employees' IT experiences, and how these factors impact employee performance.Design/Methodology/Approach: A quantitative method was employed through a survey involving 227 employees of PTNBH, examining the relationships between Individual IT Experience, Management Support, Employee IT Engagement, and Employee Performance. Research findings: The analysis reveals a strong correlation between management support, employee IT engagement and experience; all of which positively influence employee performance. Employee performance is enhanced through both direct and indirect effects of management support and individual’s experiences on IT engagement. The correlation between employees’ IT involvement and performance is statistically significant. Furthermore, the study underscores the critical role of management in promoting IT utilization for optimal performance outcomes and highlights the substantial impact of employees' individual IT experiences on their performance.Theoretical Contribution/Originality: This study contributes theoretically by presenting an integrative model and practically by providing recommendations for PTNBH managers to accelerate digital transformation success.Practitioners/Policy Implications: The practical implications include recommendations for PTNBH managers to drive digital transformation successfully.Research Limitations/Implications: The research is limited to personnel at legal entity universities. Future studies should expand the sample to include employees from universities, whether academic institutions or government agencies.